COUNTERINTUITIVENESS AND RITUAL EFFICACY IN EARLY MODERN KARELIAN HEALING: AN APPLICATION OF THE RITUAL COMPETENCE THEORY = PROTIINTUITIVNOST IN RITUALNA UČINKOVITOST V ZGODNJEMODERNEM KARELIJSKEM ZDRAVLJENJU UPORABA TEORIJE RITUALNE KOMPETENCE - Kohonen, Siria (Traditiones, 2018)
This article presents an application of Thomas E. Lawson and Robert N. McCauley’s ritual competence theory in order to study two early modern Karelian sages and their rituals, especially their healing rituals. I analyse how this application presents ritual efficacy in archived healing narratives, and how such an efficacy affects interpretations of the rituals and their performers.